Efficacy of three different alpha 1-adrenergic blockers and hyoscine N-butylbromide for distal ureteral stones - Gurbuz, M. Cenk; Polat, Haci; Canat, Lutfi; Kilic, Mert; Caskurlu, Turhan (International Brazilian journal of urology, 2011)
To evaluate hyoscine N-butyl bromide (HBB) and three different alpha-1 blockers in the treatment of distal ureteral stones. A total of 140 patients with stones located in the distal tract of the ureter with stone diameters of 5 to 10mm were enrolled in the present study and were randomized into 4 equal groups. Group 1 received HBB, Group 2 received alfuzosin, Group 3 received doxazosin and Group 4 received terazosin. The subjects were prescribed diclofenac injection (75 mg) intramuscularly on demand for pain relief and were followed-up after two weeks with x-rays of the kidneys, ureters, bladder and urinary ultrasonography every week. The number of pain episodes, analgesic dosage and the number of days of spontaneous passage of the calculi through the ureter were also recorded. The average stone size for groups 1, 2, 3 and 4 was comparable (6.13, 5.83, 5.59 and 5.48 mm respectively). Stone expulsion was observed in 11%, 52.9%, 62%, and 46% in groups 1, 2, 3 and 4 respectively. The average time to expulsion was 10.55 ± 6.21 days in group 1, 7.38 ± 5.55 days in group 2, 7.85 ± 5.11 days in group 3 and 7.45 ± 5.32 days in group 4. Alpha blockers were found to be superior to HBB (p < 0.05). Medical treatment of distal ureteral calculi with alfuzosin, doxazosin and terazosin resulted in a significantly increased stone-expulsion rate and decreased expulsion time when compared with HBB. HBB seems to have a negative effect on stone-expulsion rate.